2000
DOI: 10.1103/physrevb.61.2973
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation of silicon surfaces: Molecular-dynamics simulations of atomic force microscopy

Abstract: We investigate the atomic-scale details of atomic force microscopy through a quasistatic molecular dynamics simulation together with a density-functional-based tight-binding method. The changes in the AFM tip shape, the size of the tip-sample contact area, as well as the microscopic hardness and Young's moduli of silicon ͕111͖,͕110͖,͕100͖ surfaces are studied. Furthermore, the effects of hydrogen termination of the surface and of subsurface vacancies on hardness and Young's modulus are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…29,32,33 For silicon nanoindentation it has been reported that for penetration depths greater than 20 nm hardness values were reported to be 14.2 GPa. Thus, one of the critical steps when measuring hardness is the correct measure of the projected affected area.…”
Section: B the Plastic Region: Hardness Measurementsmentioning
confidence: 99%
“…29,32,33 For silicon nanoindentation it has been reported that for penetration depths greater than 20 nm hardness values were reported to be 14.2 GPa. Thus, one of the critical steps when measuring hardness is the correct measure of the projected affected area.…”
Section: B the Plastic Region: Hardness Measurementsmentioning
confidence: 99%
“…For example, Jarausch et al 9 used an interfacial force microscope to measure the elastic properties of 100-nm-thick gold films and found that a 50-GPa compressive stress increased the film's effective indentation modulus by 42%. Astala et al 10 combined a quasistatic molecular dynamics simulation with a density-functional-based tight-binding method to investigate indentation into silicon. At small indentation depths, they report hardness values up to 89 GPa and elastic modulus values up to 397 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…5 Indeed much of the understanding of the nanoindentation process has come about by a combination of scanning probe microscopy with classical and quantum moleculardynamics simulations. [5][6][7][8][9] The simulations have shown how elastic deformation can occur, 6 dislocations can propagate, 5,10,11 and the way in which pileup around the indentation hole 7 is formed. The deformation and defect propagation that occurs in crystals is anisotropic and when combined with a nonaxially symmetric indenter can induce a complicated overlap of mechanisms.…”
Section: Introductionmentioning
confidence: 99%